1998
DOI: 10.1021/ja973272j
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental and Quantum Chemical Investigation of CO Binding to Heme Proteins and Model Systems:  A Unified Model Based on13C,17O, and57Fe Nuclear Magnetic Resonance and57Fe Mössbauer and Infrared Spectroscopies

Abstract: We have investigated the question of how CO ligands bind to iron in metalloporphyrins and metalloproteins by using a combination of nuclear magnetic resonance (NMR), 57Fe Mössbauer, and infrared spectroscopic techniques, combined with density functional theoretical calculations to analyze the spectroscopic results. The results of 13C NMR isotropic chemical shift, 13C NMR chemical shift anisotropy, 17O NMR isotropic chemical shift, 17O nuclear quadrupole coupling constant, 57Fe NMR isotropic chemical shift, 57F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
101
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(110 citation statements)
references
References 70 publications
(278 reference statements)
8
101
0
1
Order By: Relevance
“…Earlier polarized IR measurements on various heme proteins at ambient temperature [21][22][23]25,26,28,29 reported that the orientation of CO in heme protein is bent at different angles ranging from 15 o to 35 o , similar to earlier crystal structure. 5 However, using the same polarized IR spectroscopy, we have recently found that CO in Mb is almost linear, bent less than 7 o relative to the heme plane normal, 15 consistent with more recent higher resolution X-ray crystal structure 16 and spectroscopic data in solution, 30 thereby establishing necessity of newer paradigm for how Mb discriminate against CO. Even though the theory for determining angles with photoselection spectroscopy is rigorous, there are numerous experimental pitfalls.…”
Section: Introductionsupporting
confidence: 83%
“…Earlier polarized IR measurements on various heme proteins at ambient temperature [21][22][23]25,26,28,29 reported that the orientation of CO in heme protein is bent at different angles ranging from 15 o to 35 o , similar to earlier crystal structure. 5 However, using the same polarized IR spectroscopy, we have recently found that CO in Mb is almost linear, bent less than 7 o relative to the heme plane normal, 15 consistent with more recent higher resolution X-ray crystal structure 16 and spectroscopic data in solution, 30 thereby establishing necessity of newer paradigm for how Mb discriminate against CO. Even though the theory for determining angles with photoselection spectroscopy is rigorous, there are numerous experimental pitfalls.…”
Section: Introductionsupporting
confidence: 83%
“…An upright, perpendicular geometry of the CO group is indicated by time-resolved IR polarization spectroscopy (36) of MbCO, as well as a joint analysis of NMR, 57 Fe Mössbauer, and IR data, using density functional theory (37). Any remaining discrepancy between this model and recent x-ray structures is reconciled by density functional theory calculations (38), which show that the transition dipole of the C-O stretching IR band is not coincident with the C-O bond vector, but lies between the Fe-C bond vector and the heme perpendicular.…”
Section: Proposed Mechanisms Of Ligand Discrimination In Hemementioning
confidence: 99%
“…8,9 There has been much less 17 O NMR reported from organic materials since 17 O presents even more of a challenge due to the larger quadrupole interaction and, hence, larger line widths. 19 Recent reports of 17 O NMR from biologically relevant materials have included inorganic molecules interacting with hemeproteins, 10 polypeptides, 11,12 amino acids, 2 and nucleic acid bases. 13 Here, we report the first example of 17 O NMR spectra from a selectively labeled transmembrane peptide, 17 O-[Ala12]-WALP23, as a lyophilized powder and incorporated in hydrated vesicles, opening up new possibilities for applications of 17 O solid-state NMR on real biological systems.…”
mentioning
confidence: 99%